The Infuence of Games Strategy in Teaching Structure to the First Grade Students of Madrasyah Aliyah Al-Khairiyah Pematangsiantar - Benarita Purba (Budapest International Research and Critics University, 2020)
The research aim is to know the influences of games strategy in teaching structure to the students of Madsarah Aliyah Swasta Al-Khairiyah Pematangsiantar. The type of this research is quantitative and experimental. The method of the research concerned primarily with discovering the effectiveness and the significant difference of the use of games in teaching structure. The design of this research is a true experiment design with pre-test and post-test procedure. The data were taken from the objective structure test. This research applied a random sampling technique to get samples. The total sample is 60 students. The sample is divided into two groups; the experimental group and the control group. Then, the data were analyzed using the t-test method to find out whether there is significant difference between the experimental groups taught by using games as a treatment, and the control group taught conventionally. The research results, based on the results of the analysis of Independent Samples T-Test Teaching Structure through Games to the Students and from the data analysis it was found that teaching Structure through Games is better than Teaching Structure conventionally. Besides, it can also be concluded that the t calculation value obtained (5, 12) > t table (2,021), so H0 is refused and accept the Ha, or H alternative. Thus, the hypothesis that states that “there is a significant difference between teaching structure through game and teaching structure without game” is accepted.